1659. Pharmacokinetics/pharmacodynamics of the Novel Gyrase Inhibitor SPR719/SPR720 and Clinical Dose Selection to Treat Pulmonary Mycobacterium avium-complex Disease. (31st December 2020) - Deshpande, Devyani; Kuret, Daniel; Cirrincione, Kayle; Cotroneo, Nicole; Melnick, David; Lister, Troy; Stokes, Suzanne; Gumbo, Tawanda
Abstract: Background: Current therapy for pulmonary Mycobacterium avium-complex [ MAC ] disease achieves poor sustained sputum conversion rates and is poorly tolerated. SPR719, the active metabolite of SPR720, a novel gyrase inhibitor, has demonstrated low MICs against MAC. SPR720 is being developed as an oral therapy for use in combination with other antibiotics for the treatment of patients with pulmonary disease due to infection with MAC. Our objective was identify SPR719 pharmacokinetic/pharmacodynamic [PK/PD] parameters and optimal SPR720 dose for treatment of pulmonary MAC. Methods: SPR719 was administered once daily for 28 days using a simulated human half-life of 3.3 hours in the hollow fiber system model of pulmonary intracellular MAC [HFS-MAC]. Bacterial burden, including for SPR719-resistant subpopulations, and drug concentrations, were measured via repetitive sampling of HFS-MAC units. A separate dose fractionation study in the HFS-MAC was used to identify the PK/PD index linked to effect. MAC burden versus SPR719 exposure was modeled using the inhibitory sigmoid maximal effect [Emax ] model and resistance using the "antibiotic resistance arrow of time" model. Finally, we performed Monte Carlo Experiments to identify the optimal clinical dose of SPR720 monotherapy. Results: The median HFS-MAC intracellular-to-extracellular SPR719 AUC0-24 ratio was 2300:1. The PK/PD parameter best linked to microbial kill was determined to be AUC0-24 /MIC. SPR719 Emax was -1.5 log10 cfu/mL compared to day 0; 1.0 log10 cfu/mL reduction and acquired-resistance suppression were achieved by an AUC0-24 /MIC of 2.0 and 11, respectively. SPR720 1, 000 mg/day was predicted to achieve 1.0 log10 cfu/mL kill in 95%, and resistance suppression in 43%, of 10, 000 simulated subjects. Conclusion: SPR720 monotherapy is predicted to achieve exposures associated with bactericidal effect against pulmonary MAC in 95% of patients at doses that have recently been established to be safe and well tolerated. These data support the continued development of SPR720 for the treatment of pulmonary MAC. Disclosures: Nicole Cotroneo, Spero Therapeutics (Employee) David Melnick, MD, Spero Therapeutics (Employee)Spero Therapeutics (Employee) Troy Lister, PhD, Spero Therapeutics (Employee) Suzanne Stokes, PhD, Spero Therapeutics (Employee, Shareholder) Tawanda Gumbo, MD, Praedicare Inc (Employee, Shareholder)